Price controls and optimal stabilization policy - Meyer, Laurence H.; Raines, Fredrick Q. (New York : Federal Reserve Bank of New York, 1975)
this paper is aimed to bridge the gap between theory and practice and thereby explore the coordinated application of aggregate stabilization policy and price controls to achieve desired macroeconomic goals
Includes bibliographical references
osc 08/04/2019
Loans
Keywords: Prices; Price control